Analysis of the effect of the MBKM Internship Program and Certified Independent Study (MSIB) on university performance Universitas 17 Agustus 1945 Surabaya - Susanti, Nanis; Ronando, Elsen; Basyarach, Niken Adriaty; Sulistyawati, Dwi Harini; Widiasih, Wiwin (Technium Social Sciences Journal, 2022)
Universitas 17 Agustus 1945 Surabaya as one of the leading private campuses in Indonesia has a high commitment to improving the quality of higher education. One of the efforts of the Universitas 17 Agustus 1945 Surabaya in improving the quality of higher education is through the development and improvement of every aspect of activities that refer to the Higher Education Main Performance Indicators (KPI) that have been set by the Ministry of Education and Culture. The activity program that refers to the Main Performance Indicators (IKU) is the Merdeka Learning Campus Merdeka (MBKM) activity program, which has been well implemented by the Universitas 17 Agustus 1945 Surabaya since 2019. However, in an effort to continuously improve the MBKM program, analysis is needed an in-depth look at readiness and the impact obtained at the level of study programs, faculties, and universities. One of the MBKM programs that refers to the KPI and needs to be analyzed is the Certified Independent Study & Internship MBKM program. On this basis, this study conducted an in-depth analysis of the readiness and impact of the MBKM Internship & Certified Independent Study program at the Universitas 17 Agustus 1945 Surabaya. Based on the results obtained, the level of readiness of the Universitas 17 Agustus 1945 Surabaya in supporting the MBKM program is quite good with an average percentage of readiness above 50%. In measuring the impact of MBKM, it is found that the MBKM policy, Internship Program and Independent Studies greatly affect the performance of the Universitas 17 Agustus 1945 Surabaya significantly with an impact effect of 75.4%.